Regulation of the S-Locus Receptor Kinase and Self-Incompatibility in Arabidopsis thaliana - Strickler, Susan R; Tantikanjana, Titima; Nasrallah, June B (G3 : genes - genomes - genetics, 2013)
Abstract Intraspecific mate selectivity often is enforced by self-incompatibility (SI), a barrier to self-pollination that inhibits productive pollen-pistil interactions. In the Brassicaceae, SI specificity is determined by two highly-polymorphic proteins: the stigmatic S-locus receptor kinase (SRK) and its pollen coat-localized ligand, the S-locus cysteine-rich protein (SCR). Arabidopsis thaliana is self fertile, but several of its accessions can be made to express SI, albeit to various degrees, by transformation with functional SRK-SCR gene pairs isolated from its close self-incompatible relative, Arabidopsis lyrata. Here, we use a newly identified induced mutation that suppresses the SI phenotype in stigmas of SRK-SCR transformants of the Col-0 accession to investigate the regulation of SI and the SRK transgene. This mutation disrupts NRPD1a, a gene that encodes a plant-specific nuclear RNA polymerase required for genomic methylation and production of some types of silencing RNAs. We show that NRPD1a, along with the RNA-dependent RNA polymerase RDR2, is required for SI in some A. thaliana accessions. We also show that Col-0 nrpd1a mutants exhibit decreased accumulation of SRK transcripts in stigmas, which is not, however, responsible for loss of SI in these plants. Together, our analysis of the nrpd1a mutation and of SRK promoter activity in various accessions reveals that the SRK transgene is subject to several levels of regulation, which vary substantially by tissue type and by accession. This study thus helps explain the well-documented differences in expression of SI exhibited by SRK-SCR transformants of different A. thaliana accessions.